2012
DOI: 10.1097/phh.0b013e31823dea74
|View full text |Cite
|
Sign up to set email alerts
|

Preparedness for Climate Change Among Local Health Department Officials in New York State

Abstract: Context Climate change adaptation strategies that address locally specific climate hazards are critical for preventing negative health outcomes, and local public health officials are key foci for adaptation planning. Objective To assess New York State Local Health Department officials’ perceptions and preparedness related to climate-sensitive health areas, and compare these with a national sample. Design Online survey instrument, originally used in a national survey of Local Health Department (LHD) officia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 10 publications
(13 reference statements)
0
15
0
Order By: Relevance
“…Studies indicate that many local governments do not feel adequately prepared to address the health impacts of heat [ 27 ] and, specifically, in a survey of local health departments in New York state, the majority of respondents did not feel that their department had the necessary expertise to assess potential public health risks of climate change in their jurisdiction [ 28 ]. New York, New Jersey, and Connecticut include both urban and non-urban areas and the decentralized public health structure, along with limited budgets, can mean that public health preparedness for climate change can be a challenge.…”
Section: Discussionmentioning
confidence: 99%
“…Studies indicate that many local governments do not feel adequately prepared to address the health impacts of heat [ 27 ] and, specifically, in a survey of local health departments in New York state, the majority of respondents did not feel that their department had the necessary expertise to assess potential public health risks of climate change in their jurisdiction [ 28 ]. New York, New Jersey, and Connecticut include both urban and non-urban areas and the decentralized public health structure, along with limited budgets, can mean that public health preparedness for climate change can be a challenge.…”
Section: Discussionmentioning
confidence: 99%
“…One assessment of local agencies found that the gap between the demand for health and climate interventions and the resources available to health departments was greater than in any other sector [ 28 ]. Prior surveys exploring U.S. public health officials’ perceptions and capacity for action on climate change [ 27 , 29 , 30 , 31 , 32 , 33 , 34 ] indicate that public health practitioners are aware of climate change and its effect on their jurisdiction, but report inadequate knowledge, information, planning, funding, resources, and workforce capacity to address this issue. To understand why these barriers persist and identify ways to promote engagement, we sought to understand the differences between public health practitioners currently working on climate change and those who are not.…”
Section: Introductionmentioning
confidence: 99%
“…These results have been replicated and extended in several other surveys, including surveys of the chief health officers of state and territorial health agencies [ 18 ], public health nursing administrators [ 19 ], California public health officers [ 20 ], Oregon public health officers [ 21 ], New York LHD officers [ 22 ], and environmental health directors at local, state and territorial public health agencies [ 23 ]. The results in all these surveys are similar, reporting limited preparedness for the health impacts of climate change: Half of the nursing administrators, for example, believed their departments have the responsibility to address climate-related health threats, but three-quarters said they were unprepared to do so [ 19 ].…”
Section: Introductionmentioning
confidence: 78%